2018
DOI: 10.1002/phar.2194
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Use of Cidofovir and Intravenous Immunoglobulin to Treat Invasive Adenoviral Disease in Solid Organ Transplant Recipients

Abstract: Background Infections with adenoviruses (ADVs) can result in considerable mortality and morbidity in solid organ transplant (SOT) recipients. Standard therapy for ADV infections in transplant recipients is not established. At our institution, intravenous cidofovir and immunoglobulin have been used to treat disseminated or invasive ADV in SOT and hematopoietic stem cell transplant recipients. Methods A retrospective case series of SOT recipients treated with cidofovir and intravenous immunoglobulin was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In our cohort, 21 patients were treated with cidofovir. Although data from large randomised controlled trials are lacking and standard therapy for adenovirus infections is not yet established, cidofovir has been shown to be an acceptable treatment for an adenovirus infection in patients with various conditions such as after solid organ transplants 24 and hematopoietic stem cell transplants 25 . However, data are scarce, yet positive, regarding cidofovir treatment in previously healthy people with severe illness 7,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, 21 patients were treated with cidofovir. Although data from large randomised controlled trials are lacking and standard therapy for adenovirus infections is not yet established, cidofovir has been shown to be an acceptable treatment for an adenovirus infection in patients with various conditions such as after solid organ transplants 24 and hematopoietic stem cell transplants 25 . However, data are scarce, yet positive, regarding cidofovir treatment in previously healthy people with severe illness 7,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been reported that ribavirin and cidofovir treatment [ 41–44 ] and adoptive transfer of Ad-specific T cells [ 45, 46 ] effectively prevented Ad infections in patients following transplantation. Intravenous immunoglobulin (IVIG) has been used to treat severe Ad infection in combination with ribavirin and cidofovir [ 47–49 ], but the therapeutic effects of IVIG itself are unclear [ 50 ]. Our results suggest that the effect of IVIG is attenuated by progeny Ad in the presence of nAb and that inhibition of this infection is an attractive strategy for patients treated with IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG is being used in the treatment of other viral illnesses that affect the immunocompromised renal transplant population. In a small five patients study cidofovir in combination with IVIG was found to be helpful in clearing disease for patients with invasive adenovirus infection …”
Section: Discussionmentioning
confidence: 99%